Pimozide Inhibits the Human Prostate Cancer Cells Through the Generation of Reactive Oxygen Species - Kim, Ukjin; Kim, C-Yoon; Lee, Ji Min; Ryu, Bokyeong; Kim, Jin; Shin, Changsoo; Park, Jae-Hak (Frontiers in Pharmacology, 2020)
The United States Food and Drug Administration-approved antipsychotic drug, pimozide, has anticancer activities. However, the role of reactive oxygen species (ROS) in its effect on prostate cancer is not well-known. We examined cell proliferation, colony formation, migration, ROS production, and the expression of antioxidant-related genes after treatment of human prostate cancer PC3 and DU145 cells with pimozide. In addition, histopathology, ROS production, and superoxide dismutase (SOD) activity were analyzed after administering pimozide to TRAMP, a transgenic mouse with prostate cancer. Pimozide increased the generation of ROS in both cell lines and inhibited cell proliferation, migration, and colony formation. Oxidative stress induced by pimozide caused changes in the expression of antioxidant enzymes (SOD1, peroxiredoxin 6, glutathione peroxidase 2) and CISD2. Co-treatment with glutathione, an antioxidant, reduced pimozide-induced ROS levels and counteracted the inhibition of cell proliferation. Administration of pimozide to TRAMP mice reduced the progression of prostate cancer with increased ROS generation and decreased SOD activity. These results suggest that the antipsychotic drug, pimozide, has beneficial effects in prostate cancer in vivo and in vitro. The mechanism of pimozide may be related to augmenting ROS generation. We recommend pimozide as a promising anticancer agent.